Plant‐Plant Interactions Drive the Decomposition of Soil Organic Carbon via Nutrition Competition in Dryland - Wang, Wei; Li, Meng‐Ying; Wen, Qing‐Hui; Mo, Fei; Ren, Ai‐Tian; Duan, Hai‐Xia; Tao, Hong‐Yan; Li, Jian‐Ming; Cao, Jing; Sheteiwy, Mohamed S.; Xiong, You‐Cai (Plant, cell and environment, 2025)
ABSTRACT Plant‐plant interactions are often overlooked when assessing carbon (C) cycling in plant community. Limited research exists on how nutrient competition influences soil organic carbon (SOC) dynamics via modifying rhizosphere C turnover. To address this issue, quantitative model of plant–plant interactions was established in three intercropping systems across 4 years. Key variables, including plant growth rate, relative interaction intensity, C retention, root and microbial‐driven C emissions, rhizosphere priming effects (RPE), and extracellular enzyme activities, were quantified. Superior species exhibited significantly higher growth rate, photosynthetic fixed C retained in roots and rhizodeposition, and root respiration, but lower RPE (31.9%) relative to monocultures. Such trend was tightly associated with significant reduction of microbial mineralization caused by rhizosphere nitrogen and phosphorus enrichment. In contrast, due to low nitrogen and phosphorus availability in rhizosphere soils, the activities of rhizosphere extracellular hydrolase of inferior species increased, resulting in significant increase in RPE (21.9%) and decrease in photosynthetic fixed C from rhizodeposition. Therefore, plant‐plant interactions are crucial in regulating SOC turnover in rhizosphere soils, and superior species can enhance soil C conservation by increasing root C inputs and suppressing RPE. These findings confirm the role of plant‐plant interactions in SOC turnover in dryland intercropping systems. Summary Statement This study demonstrates that superior species suppress rhizosphere priming effects through nutrient enrichment, thereby enhancing C retention, while inferior species stimulate C mineralization under nutrient scarcity, resulting in C loss. These findings elucidate novel mechanisms governing SOC turnover dynamics within plant communities.